2005
DOI: 10.1007/bf02985582
|View full text |Cite
|
Sign up to set email alerts
|

A case of diffuse hepatic angiosarcoma diagnosed by FDG-PET

Abstract: A 76-year-old woman was admitted to our hospital with a 2-month history of increasing abdominal distension, leg edema, and dyspnea. The serum transaminase level was about twice the upper limit of normal. The CT showed no tumor. Fluorine-18 2-deoxy-2-fluoro-D-glucose (FDG)-positron emission tomography (PET) showed diffuse abnormal accumulation throughout the entire liver. She was diagnosed by histopathological examination as having hepatic angiosarcoma causing veno-occlusive disease (VOD). This is the first rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Subjects with malignancy or known liver diseases which can affect hepatic FDG uptake (hepatitis [10], lymphoma [11] and hepatic angiosarcoma [12]) were excluded. Blood sampling was done to check aspartate arminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH).…”
Section: Patientsmentioning
confidence: 99%
“…Subjects with malignancy or known liver diseases which can affect hepatic FDG uptake (hepatitis [10], lymphoma [11] and hepatic angiosarcoma [12]) were excluded. Blood sampling was done to check aspartate arminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH).…”
Section: Patientsmentioning
confidence: 99%
“…The sensitivity of PET scanning for diagnosing soft tissue and bone sarcomas ranges 83–93% and is greater for high‐ and intermediate‐grade sarcomas . To our knowledge, there were only a few reports of HAS detected by FDG‐PET and PET/CT . The present case is the first to use FDG‐PET and Gd‐EOB‐DTPA‐MRI for primary staging of HAS.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge there are only a few reports about angiosarcomas at uncommon localizations (cardiac, hepatic and venous regions) detected by FDG PET and PET/CT (1,7,8,9,10) and the value of FDG PET in diagnosis and staging was well-defined in these studies. However, early detection of local and/or distant metastases is a challenging problem in high-risk patients and has an important role to predict the patients’ outcomes.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…There are some studies that reported the use of FDG PET and PET/CT in angiosarcomas (hepatic, cardiac, venous and cutaneous angiosarcomas) in the literature (1,6,7,8,9,10,11). In this paper, we aimed to report the potential benefits of F18-FDG PET/CT imaging in two angiosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%